Eliminate obstacles of use the solar systems as buildings facades using multilayers optical interference filters - AL-Assadi, Zainab I.; Asadi, Fawzia; Alameri, Ban M. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The Building design in a correct way and totalitarian requires integration of using solar energy technologies in the architectural design stage of the roofs and facades as the most appropriate places to obtain solar energy because it greatly affects the architectural aesthetic. This integration has to be taken into account at the design stage, which leads to effective and attractive solutions. Architecture needs the energy to complete its functions to increases human effectiveness and ability to do its tasks better, solar energy is the main factor of providing the necessary energy due to its abundance as well as being clean energy and does not cause polluting emissions to the environment. To provide a comfortable indoor environment for the occupants, Solar Thermal Collectors (STC) and Photovoltaics Cells (PV) used, which convert solar energy into thermal energy and electrical energy, respectively. The main problem of this study is concerning with the problems of the black color, visible tubes, metallic strip gradients (absorption strip), and welding points of the solar systems which gives the facades of the buildings an undesirable view and weakens the aesthetic aspect of the buildings and limits the abilities of architects to use because of their black color and undesirable aspect. The aim of this study is a design of optical interference filter (multilayer coatings) prepared by RF magnetron sputtering as a solution to the problem of black color, visible tubes, metallic strip gradients (absorption strip), and welding points in solar thermal collectors and photovoltaic cells, which are the main reasons for not using solar systems as building facades, this technique works to increase the efficiency of the solar systems and increase the amount of clean energy generated, also enhancing the expressive and aesthetic aspect of facades of buildings. In the NIR region this filter works as an anti-reflective coating. Also the coating includes a high color reflection at a certain wavelength in the VIS region to give the solar system an aesthetic feature, which is used as building facades by using appropriate dielectric substances with high and low reflective indexes likes SiO2 and MgF2 respectively. The results of the study showed that the increase in the number of layers will lead to an increase in the visible reflectivity peak, while near of infrared region remains an anti-reflective with a high Transmission of solar rays, thus increasing solar systems efficiency.